The Cytokine and Bone Protein Expression by Ellagic Acid-Hydroxyapatite in Bone Remodelling Model - Dyah Noviana Primasari; Intan Nirwana; Hendrik Setia Budi; Agung Satria Wardhana; Annisa Fitria Sari; Novita Novita; Andika Putri Setyawan; Meircurius Dwi Condro Surboyo; Khairul Anuar Shariff (The Scientific World Journal)
Objective. Ellagic acid, a phenolic compound with anti-inflammatory potential, can be used to accelerate the bone healing process and affect human health, while hydroxyapatite is the most commonly used bone graft material. Using a combination of the two materials results in reduced inflammation and increased osteogenesis. This study aimed to determine the effects of combining ellagic acid and hydroxyapatite in bone marker remodelling by analysing the expression of tumour necrosis factor-α (TNF-α), interleukin 10 (IL-10), bone morphogenetic 4 protein (BMP-4), and osteopontin (OPN). Methods. Thirty Wistar rats were used in the study. A defect was created in each animal’s femur using a low-speed diamond bur. In the control group, the bone was then treated with polyethylene glycol (PEG). In one of the other groups, the bone was treated with hydroxyapatite, and in the other, with ellagic acid-hydroxyapatite. The femur was biopsied 7 days after the procedure and again 14 days after the procedure, and an indirect immunohistochemical (IHC) examination was performed for TNF-α, IL-10, BMP-4, and OPN expression. Results. The ellagic acid-hydroxyapatite decreased TNF-α expression in the bone tissue after 7 days and again after 14 days (p < 0.05). On the other hand, it increased IL-10, BMP-4, and OPN expression (p < 0.05) during the same time periods. Conclusion. Ellagic acid-hydroxyapatite plays a role in bone marker remodelling by decreasing the expression of TNF-α and increasing the expression of IL-10, BMP-4, and OPN. This hydroxyapatite combination can therefore be recommended for use as bone graft material.